2019
DOI: 10.24843/jmas.2019.v05.i02.p04
|View full text |Cite
|
Sign up to set email alerts
|

Tingkat dan laju penurunan kualitas air di DAS Brantas Malang Raya

Abstract: The decrease level of water quality of Brantas Watershed in Malang Raya was observed in this study. The aim of this study was to observe the decrease level of water quality of Brantas Watershed from Batu to Malang City. This study was carried out in the Brantas Watershed of Malang Raya (8 stations: A, B, C, D, E, F, G, and H) for 18,4 Km. The water quality parameters observed in this study were: CODmn (permanganometry), CODcr (CODmn correlation based analysis), dissolved oxygen (DO) (Winkler iodometry), TDS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…This may indicate that the pollutant was significant enough to deplete the dissolved oxygen. This condition makes the organic substances unable to decompose into inorganic substances since the oxidant is the limiting unit [16]. At this point, it can be concluded that the capacity for COD and BOD pollution load in the river has reached its limit.…”
Section: Brantas River Water Qualitymentioning
confidence: 98%
“…This may indicate that the pollutant was significant enough to deplete the dissolved oxygen. This condition makes the organic substances unable to decompose into inorganic substances since the oxidant is the limiting unit [16]. At this point, it can be concluded that the capacity for COD and BOD pollution load in the river has reached its limit.…”
Section: Brantas River Water Qualitymentioning
confidence: 98%
“…The agencies involved in monitoring the water quality in the Brantas Watershed are the East Java Province Public Works Office, Bapedal, Ditjen PPKL, and Perum Jasa Tirta I. According to the observation conducted in the upstream Brantas for the four water quality parameters, i.e., pH, DO, COD, and TDS [54,55], there was a decreasing trend in COD from 2017 to 2019; conversely, the TDS increased. This condition indicates a rise in dissolved solids in the upstream Brantas waters, which may interfere with water use in the Brantas since, at some levels, it will be hazardous to use owing to continuous exposure to chemicals.…”
Section: Pollution Of Brantas River East Java Provincementioning
confidence: 99%
“…Kandungan bahan organik pada media air dapat direduksi melalui manajemen kualitas air yang baik, seperti: ammonia, nitrit dan nitrat (Yuningsih et al, 2014). Mekanisme konversi berlangsung dalam kondisi aerob melalui proses nitrifikasi (Hastuti, 2011) dengan produk total dissolved solid (TDS) (Haryani dan Kartika, 2014;Perwira, 2019).…”
Section: Pendahuluanunclassified